Activation of adenosine receptors improves renal antioxidant status in diabetic Wistar but not SHR rats. (March 2014) - Patinha, Daniela; Afonso, Joana; Sousa, Teresa; Morato, Manuela; Albino-Teixeira, António
Abstract Background. Diabetes and hypertension independently contribute to renal injury, and the major mechanisms involved are increased reactive oxygen species (ROS) bioavailability and renin-angiotensin system (RAS) activation. We investigated the role of adenosine in controlling ROS production and RAS activation associated with renal dysfunction in hypertension and diabetes. Methods. Fourteen days after induction of diabetes with streptozotocin in 12-week-old male Wistar and spontaneously hypertensive (SHR) rats, animals were treated during 7 days with 2-chloroadenosine (CADO group, 5 mg/kg/d), a stable analogue of adenosine, or underwent a sham operation procedure. At the end of the study (day 21), intra-arterial systolic blood pressure (SBP) was measured, and 24-h urine and plasma samples and renal tissue were collected. Results. CADO treatment decreased the plasma glucose concentration and glucose and protein excretion by more than 30% in both strains. CADO treatment decreased SBP in diabetic SHR rats (143 ± 8 versus 114 ± 4 mmHg, p < 0.05), but not in diabetic Wistar rats. The hypotensive effect of CADO was associated to a ∼70% increase in plasma angiotensinogen (AGT) concentration and a ∼50% decrease in urinary AGT excretion. CADO also caused a decrease in medullary and cortical hydrogen peroxide production of about 40%, which was associated with a proportional increase in glutathione peroxidase (GPx) activity in diabetic Wistar but not in diabetic SHR animals. Conclusions. These results suggest that activation of adenosine receptors improves renal antioxidant capacity in diabetic Wistar but not SHR rats, although it improves glucose metabolism in both strains. Furthermore, activation of adenosine receptors does not seem to be directly influencing AGT production.